Successful bone marrow transplantation in a patient with Omenn syndrome, a rare variant of severe combined immunodeficiency syndrome: A case report - Ubaid Khan (12476186) (2024)
Key Clinical Message Bone marrow transplantation (BMT) saves lives in Omenn syndrome, a severe immunodeficiency disorder. Timely genetic diagnosis and matched donor BMT are crucial. Emphasis on newborn screening and multidisciplinary care improves outcomes for infants with inherited disorders. Prompt intervention and comprehensive management are vital for a successful transplant outcome. Omenn syndrome represents a severe variant of combined immunodeficiency characterized by disregulated immune responses and susceptibility to recurrent infections. We present the case of a 3‐month‐old female infant initially presenting with upper respiratory infection symptoms and a diffuse rash, unresponsive to local treatment. At 4 months of age, the patient underwent allogeneic bone marrow transplantation (BMT) utilizing stem cells from a fully matched sibling donor. Pre‐transplant conditioning included antimicrobial prophylaxis and supportive therapies. Following BMT, the patient received immunosuppressive medications to prevent graft rejection and graft‐versus‐host disease. Clinical monitoring post‐transplant showed timely neutrophil and platelet engraftment, with subsequent follow‐up demonstrating stable clinical parameters and negative cytomegalovirus status. The case highlights the importance of timely diagnosis and treatment in managing severe immunodeficiency disorders, demonstrating the potential for successful outcomes with appropriate timely interventions. Regular monitoring and follow‐up appointments were crucial in ensuring the success of the treatment. This case also emphasizes the significance of multidisciplinary care and genetic testing in identifying and managing rare immunodeficiency disorders. The successful outcome in this case provides hope for improved treatment options and better patient outcomes in the future. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9295